DIE'l'ARY CHOLESTEROL REQUIREMENT OF LARVAE AND POSTLARVAE OF THE PRAWN PENAEUS INDICUS (H. MILNE EDWARDS) - PAULRAJ, R.; CHANDGE, M. S. (Journal of Indian Fisheries Association, 2015)
Two sets of experiments were conducted to determine the dietarycholesterol requirement of larvae and postlarvae 1~10 of Penaeus indicus.Seven approximately isocaloric and isonitrogenous purified experimentaldiets were tried with graded levels of cholesterol ranging from 0 to 4%.The control feed for larvae and postlarvae 1~10 were phytoplankton andcompounded feed NPCLÂ·17, developed by CMFRI, Cochin respectively.Result of these experiments indicate that cholesterol is an essentialÂ·nutrient in the diet of larvae and postlarvae 1-10. Survival and growth oflarvae and postlarvae 1-10 were greatly affected by cholesterol deficiencyin the diet. The optimal cholesterol requirement for larvae appeared tobe 0.5% of the diet, while it was higher for postlarvae where inclusion ofcholesterol at a level of 2% in the diet gave higher growth.